2017
DOI: 10.1093/intimm/dxx075
|View full text |Cite
|
Sign up to set email alerts
|

How to master the host immune system?Leishmaniaparasites have the solutions!

Abstract: Host immune response to Leishmania parasites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
155
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(165 citation statements)
references
References 100 publications
1
155
0
9
Order By: Relevance
“…Strain comparisons within and between countries are, however, complicated by the large number of methods and sequences used, and there is a clear need for unification and standardization of molecular markers for a better understanding of Leishmania epidemiology (Akhoundi et al, 2017;van der Auwera & Dujardin, 2015;Schönian, Kuhls, & Mauricio, 2010). There is little evidence so far for a strong association between L. infantum infection in humans with specific variants and certain clinical forms, partly because the tropism of this species for the skin or for multiple internal organs (i.e., cutaneous/visceral forms) is mostly influenced by the host immune response (Alvar, 1994;Gradoni & Gramiccia, 1994;Rossi & Fasel, 2018 I II I II III IV I II III I II III IV V I II III New pattern discovered in this study for RsaI enzyme, named III, as this name for RsaI enzyme has not been previously used.…”
Section: Discussionmentioning
confidence: 99%
“…Strain comparisons within and between countries are, however, complicated by the large number of methods and sequences used, and there is a clear need for unification and standardization of molecular markers for a better understanding of Leishmania epidemiology (Akhoundi et al, 2017;van der Auwera & Dujardin, 2015;Schönian, Kuhls, & Mauricio, 2010). There is little evidence so far for a strong association between L. infantum infection in humans with specific variants and certain clinical forms, partly because the tropism of this species for the skin or for multiple internal organs (i.e., cutaneous/visceral forms) is mostly influenced by the host immune response (Alvar, 1994;Gradoni & Gramiccia, 1994;Rossi & Fasel, 2018 I II I II III IV I II III I II III IV V I II III New pattern discovered in this study for RsaI enzyme, named III, as this name for RsaI enzyme has not been previously used.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages produce IL-12 to promote a Th1 response during leishmanial infection, which protects the host and controls parasite replication [30,31]. Meanwhile, TNF-α and IFN-γ, implicated to be involved in the activation of macrophages, were also observed to play a role in preventing parasite replication [32]. Previous studies also verified that drugs which have inhibitory effects on L. donovani, could decrease IL-10 and IL-4 in VL mice [4,33,34].…”
Section: Discussionmentioning
confidence: 97%
“…A first set of assays showed that Asaia WSP indeed activates an antibacterial response in macrophages, on both Asaia itself and on S. epidermidis . The study was then focused on Leishmania , an intracellular parasite that targets monocytes and macrophages (Antoniou et al, 2013;Rossi & Fasel, 2018). The experiments were realized using a macrophage cell line derived from a Leishmania -susceptible mice strain.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a M2 response is associated with anti-inflammatory cytokine production, such as IL-4/IL-13, IL-10, TGFβ, M-CSF, expression of arginase I (with reduced NO production), inhibition of inflammation, parasite survival, and thus disease progression. In summary, while M1 activation is crucial for a successful elimination of Leishmania parasites, the M2 polarization, besides being unprotective, is in general associated with disease severity, also in relation with immune-complex pathology (Rossi & Fasel 2018). Therefore, one of the major aims in leishmaniasis research is the identification of molecules with immunotherapeutic properties, i.e.…”
Section: Introductionmentioning
confidence: 99%